Asymmetric synthesis of the cytotoxic lactone (+)-cardiobutanolide and two novel analogues. Issue 9 (28th February 2019) - Kovačević, Ivana; Popsavin, Mirjana; Rodić, Marko V.; Kojić, Vesna; Popsavin, Velimir
Graphical abstract: Highlights: A new total synthesis of cardiobutanolide and two new analogues has been completed. In vitro antitumour activity of this natural product and analogues was recorded. (+)-Cardiobutanolide was identified as the most active compound. Abstract: A new asymmetric synthesis of the naturally occurring styryl lactone cardiobutanolide and two novel analogues have been achieved starting fromd -xylose. The key steps of the synthesis included an initial zinc mediated reductive THF-ring opening, stereoselective olefination and Sharpless asymmetric dihydroxylation. It was shown that cardiobutanolide (1 ) exhibits promising in vitro antitumour properties against certain human neoplastic cell lines. It was more potent than the commercial anticancer agent doxorubicin against three cell lines (K562, HL-60 and Raji).